Distraction and Mind-Wandering Under Load - Forster, Sophie (Frontiers in Psychology, 2013)
Attention research over the last several decades has provided rich insights into the determinants of distraction, including distractor characteristics, task features and individual differences. Load Theory represented a particularly important breakthrough, highlighting the critical role of the level and nature of task load in determining both the efficiency of distractor rejection and the stage of processing at which this occurs. However, until recently studies of distraction were restricted to those measuring rather specific forms of distraction by external stimuli which I argue that, although intended to be irrelevant, were in fact task-relevant. In daily life, attention may be distracted by a wide range of stimuli, which may often be entirely unrelated to any task being performed, and may include not only external stimuli but also internally generated stimuli such as task-unrelated thoughts. This review outlines recent research examining these more general, entirely task-irrelevant, forms of distraction within the framework of Load Theory. I discuss the relation between different forms of distraction, and the universality of load effects across different distractor types and individuals.